Physical Layer Encryption Algorithm Based on Polar Codes and Chaotic Sequences - Xinjin Lu; Jing Lei; Wei Li; Ke Lai; Zhipeng Pan (IEEE Access, 2019)
Researches on 5th generation mobile communication networks (5G) are emerging to meet the demands of rapidly developing communications applications. The reliability and security of data have become key factors of its development, and thus 5G has put forward higher requirements for new coding and encryption technologies. In this paper, a physical layer encryption algorithm based on polarization codes and chaotic sequences is proposed to improve the reliability and confidentiality of transmission. In our scheme, chaotic sequences are allocated in the frozen bits of polar codes. Therefore, error correction and encryption can be performed simultaneously. Since the frozen bits are unknown to the eavesdroppers, it is difficult for them to decode the transmitted bits without the knowledge of the chaotic sequences. To further improve the security, we propose to generate the chaotic sequences by using the channel state information. Besides, the chain effects of delayed feedback are applied to increase the decrypted complexity of the eavesdroppers in this paper. Theoretic analysis and simulation results both show that the proposed algorithms can achieve high security without any error rate performance loss.